2013
DOI: 10.3758/s13414-013-0431-3
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of event files can be conceptually mediated

Abstract: Distractor-based retrieval of event files was assessed with a sequential priming experiment using a four-choice identification task. Pictures or sounds of four different animals (frog, chicken, lamb, singing bird) had to be categorized by pressing one of four keys. On each trial, a target and a distractor stimulus were presented simultaneously in different modalities. The relevant modality switched randomly between trials. Distractor repetition effects were modulated by the response relation between the prime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 31 publications
(37 reference statements)
4
49
2
Order By: Relevance
“…task, decision, action), the level of stimulus processing that is associated to the components remains unclear. There have been some studies supporting a relatively abstract stimulus representation (Biederman & Cooper, 1991;Biederman & Gerhardstein, 1993;Cave, Bost, & Cobb, 1996;Fiser & Biederman, 2001;Frings, Moeller, & Rothermund, 2013;Furmanski & Engel, 2000;Saggar, Miikkulainen, & Schnyer, 2010) but other studies have found support for some degree of stimulus specificity (Horner & Henson, 2011b;Schnyer et al, 2007;Srinivas, 1993;Vuilleumier, Henson, Driver, & Dolan, 2002). The purpose of the present study was to further our understanding of stimulus-response associations by investigating how the hierarchical modules on both sides of the association link interconnect.…”
Section: Introductionmentioning
confidence: 91%
“…task, decision, action), the level of stimulus processing that is associated to the components remains unclear. There have been some studies supporting a relatively abstract stimulus representation (Biederman & Cooper, 1991;Biederman & Gerhardstein, 1993;Cave, Bost, & Cobb, 1996;Fiser & Biederman, 2001;Frings, Moeller, & Rothermund, 2013;Furmanski & Engel, 2000;Saggar, Miikkulainen, & Schnyer, 2010) but other studies have found support for some degree of stimulus specificity (Horner & Henson, 2011b;Schnyer et al, 2007;Srinivas, 1993;Vuilleumier, Henson, Driver, & Dolan, 2002). The purpose of the present study was to further our understanding of stimulus-response associations by investigating how the hierarchical modules on both sides of the association link interconnect.…”
Section: Introductionmentioning
confidence: 91%
“…Frings et al (2013) used pictures and sounds of animals as distractors. Distractor repetition trials were realized via repetition of animal identity, while distractor modality could change (e.g., from a picture to a sound).…”
Section: Discussionmentioning
confidence: 99%
“…Distractor-based retrieval of S-R episodes has been shown with different stimuli (e.g., words, colours, pictures; Frings et al, 2007;Frings, Moeller, & Rothermund, 2013;Hommel, 1998;Hommel & Colzato, 2009;Mayr & Buchner, 2006;Moeller & Frings, 2011;Moeller, Rothermund, & Frings, 2012;Rothermund et al, 2005). However, in nearly all studies investigating distractorresponse binding effects, distractor repetition always implied a perceptually exact repetition of the distractor (see Frings et al, 2013, for an exception).…”
mentioning
confidence: 99%
“…Hence, repeating a stimulus that was earlier integrated in an action plan leads to response facilitation if the same response has to be repeated and, conversely, it leads to response impairment if a different response is required. Research on stimulus-response bindings in general has uncovered a wide variety of stimulus-response associations that are integrated automatically (Frings et al, 2007;Frings, Moeller, & Rothermund, 2013;Hommel, 1998Hommel, , 2004Hommel et al, 2004;Horner & Henson, 2009, 2011Mayr & Buchner, 2006;Logan, 1988Logan, , 1990Waszak, Hommel, & Allport, 2004, for a recent review on stimulus-response binding in general, see Henson, Eckstein, Waszak, Frings, & Horner, 2014). The fact that not only currently relevant information is associated to own responses, but also additional response-irrelevant features, indicates that action plans readily accommodate any kind of environmental contingency.…”
Section: Binding Responses and Concurrent Distractor Stimulimentioning
confidence: 99%